(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
This paper presents the design and executes a Dual Axis light tracking system. The system is designed to track the light in order to get maximum intensity from the light intensity sensor (L.I.S) GY-30 as they follow the direction light incident on it by using two servo motors, the motors can be rotate from (0o-180o) in four directions. This system consist of (L.I.S) and four LDRs where as it has been designed as shape like a cross and we fixed the (L.I.S) and LDRs then putted on a stand which fixed on plastic box that contain all work requirements. The LDRs have been employed to sense direction of the light which is directly connected to microcontroller (MCU) embedded in Arduino Mega. The MCU therefore commands any one of two Servo motor to re-orient the (L.I.S) either vertically or horizontally in order to stay straight to the light. The data of lux is display in the same time on LCD and on the PC by serial monitor or recorded on the Database for Excel, moreover the executing cost is (20) which is relatively cheap. The system is programmed with Arduino IDE. Based on the results, the three cases proved efficiency, accuracy, reliability, and durability for our not expensive, and easy to maintain the system.